Rinoneumonitis Equina : un riesgo para la cría y la salud de la población equina colombiana (2004)
ABSTRACT: Equine Rhinopneumonitis is an ample term by means of it, is described one of the more serious contagious diseases than can suffer our horses. It is the result of the infection by a virus of the Herpesviridae family, being responsible for the disease two types: Equine Herpesvirus-1 and 4 (EHV-1 and EHV-4). Both are of world-wide distribution and are potential risk factors for horses of all ages and categories, particularly the colts. The infection by EHV-1 and EHV-4 is characterized by a primary infection in respiratory tract, which can vary of moderate to severe according to the immunological state of the infected animal. The infection by EHV-1 particularly, can progress through the mucus respiratory and get to cause to abortions in the last months of gestation, perinatal death of colts, and even nervous sings. In many occasions the primary infection by EHV-1 and EHV-4 this followed by a state of viral latency, in which the horses are totally healthy. After a stress situation (means transport, enviromental changes, pregnancy, etc.) the virus can reactivate itself in these infected animals and infect other healthy horses. For the identification of the infected animals, a great amount of techniques exists, being the most appropriate the viral isolation, followed of a serologic confirmation of the virus. This can be isolated of nasal secretions, during the infection in respiratory tract, also of samples of liver, lung, spleen or thymus of the aborted fetuses and a simple blood sample taken to the animal in the acute phase of the disease. There are actually reports of the disease in our country, but the necessary measures are not even taken to resist their possible damages and injuries, as much for the equine industry as for the national economy.